PENINGKATAN TANGGUNG JAWAB INDIVIDU MELALUI METODE KOOPERATIF TIPE JIGSAW PADA SISWA KELAS VIII SMP MATA PELAJARAN IPS - Sendi Ristianto; Syamsul Bachri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Low individual responsibility in collaborative learning remains a challenge in Social Studies (IPS) instruction, as some students have not yet participated optimally in completing group tasks. This study aimed to enhance students' individual responsibility through the implementation of the Jigsaw cooperative learning model. The research employed a Classroom Action Research design based on the Kemmis and McTaggart model, consisting of two cycles involving 32 students from Class VIII-D of SMP Negeri 4 Malang. Each cycle comprised the stages of planning, implementation, observation, and reflection. Data were collected using an observation checklist completed by two observers. Individual responsibility was assessed through five behavioral indicators: mastery of the learning material, active participation in the expert group, timely completion of assigned tasks, active participation in the home group, and the ability to evaluate and motivate one's own role. The data were analyzed using descriptive quantitative analysis with percentage calculations. The findings revealed that the average level of students' responsibility increased from 53% in Cycle I to 87% in Cycle II, indicating that all predetermined success criteria were achieved. These findings suggest that the implementation of the Jigsaw cooperative learning model enhanced students' individual responsibility by positioning every group member as an essential contributor to collaborative knowledge construction. Therefore, the model has the potential to serve as an alternative instructional strategy for Social Studies learning to strengthen students' sense of responsibility in line with the implementation of the Merdeka Curriculum and the Pancasila Student Profile. ABSTRAK Rendahnya tanggung jawab individu dalam pembelajaran kolaboratif masih menjadi tantangan pada pembelajaran IPS karena sebagian peserta didik belum berpartisipasi secara optimal dalam menyelesaikan tugas kelompok. Penelitian ini bertujuan meningkatkan tanggung jawab individu peserta didik melalui penerapan model pembelajaran kooperatif tipe Jigsaw. Penelitian menggunakan pendekatan Penelitian Tindakan Kelas (Classroom Action Research) model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus pada 32 peserta didik kelas VIII-D SMP Negeri 4 Malang. Tindakan pada setiap siklus meliputi tahap perencanaan, pelaksanaan, observasi, dan refleksi. Data diperoleh melalui lembar observasi yang diisi oleh dua orang pengamat. Tanggung jawab individu diamati berdasarkan lima indikator, yaitu penguasaan materi, partisipasi dalam kelompok ahli, penyelesaian tugas tepat waktu, partisipasi dalam kelompok asal, serta kemampuan mengevaluasi dan memotivasi peran diri. Analisis data dilakukan secara deskriptif kuantitatif menggunakan persentase. Hasil penelitian menunjukkan bahwa rata-rata tanggung jawab peserta didik meningkat dari 53% pada Siklus I menjadi 87% pada Siklus II sehingga seluruh indikator keberhasilan penelitian tercapai. Temuan tersebut menunjukkan bahwa penerapan model pembelajaran kooperatif tipe Jigsaw mampu meningkatkan tanggung jawab individu peserta didik melalui pembelajaran kolaboratif yang menempatkan setiap anggota kelompok sebagai bagian penting dalam proses berbagi pengetahuan. Model ini berpotensi menjadi alternatif strategi pembelajaran IPS untuk mendukung penguatan karakter tanggung jawab sejalan dengan implementasi Kurikulum Merdeka dan Profil Pelajar Pancasila.